2014
DOI: 10.1098/rsif.2013.0814
|View full text |Cite
|
Sign up to set email alerts
|

Fish responses to flow velocity and turbulence in relation to size, sex and parasite load

Abstract: Riverine fish are subjected to heterogeneous flow velocities and turbulence and may use this to their advantage by selecting regions that balance energy expenditure for station holding while maximizing energy gain through feeding opportunities. This study investigated microhabitat selection by guppies Poecilia reticulata in terms of flow characteristics generated by hemisphere boulders in an open channel flume. Velocity and turbulence influenced the variation in swimming behaviour with respect to size, sex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 58 publications
5
59
1
1
Order By: Relevance
“…Karino et al (2006), in addition to showing that the guppies with longer tails exhibiting poorer swimming performances, have also shown that these long-tailed guppies are restricted into low water flow velocity microhabitats in streams. The investigation of Hockley et al (2014) also support the above findings of Karino et al (2006). All these findings suggest an interesting ecological phenomenon of 'habitat partitioning' (Hutchinson 1959) among the wild, yellow and black guppies if they were allowed to co-occur in streams.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Karino et al (2006), in addition to showing that the guppies with longer tails exhibiting poorer swimming performances, have also shown that these long-tailed guppies are restricted into low water flow velocity microhabitats in streams. The investigation of Hockley et al (2014) also support the above findings of Karino et al (2006). All these findings suggest an interesting ecological phenomenon of 'habitat partitioning' (Hutchinson 1959) among the wild, yellow and black guppies if they were allowed to co-occur in streams.…”
Section: Discussionsupporting
confidence: 75%
“…For example, the yellow guppies had higher standard length than that of the black guppies. Hockley et al (2014) showed that guppies with increased standard length were more active and spent more time in areas of both high velocity and low velocity water flow. Although longer fins serve as secondary sex characteristics in guppies, the larger fins increased the hydrodynamic drag compared to smaller fins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wake region of an AR is formed by the interaction of the reef with prevailing currents or water flows (Wolanski and Hammer, 1988). Wake regions have a high probability of recruiting seaweed spores or attracting marine species because they facilitate energy saving zones for marine species (Liao et al, 2003;Beal et al, 2006;Hockley et al, 2013) and deposition of sediments, nutrients, and bio-deposits (Sawaragi, 1995;Miller et al, 2002;Falcão et al, 2007;Prairie et al, 2012). In general, the wake region of an AR is defined as the space consisting of the recirculating water flow immediately behind the AR (Sheng, 2000;Oh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Second, a certain reef function should be established to increase living marine resources and biomass, otherwise the initial goal cannot be partially or even completely achieved. This function is categorized into several elements such as gathering or attracting marine species, providing a rest, spawning, and energysaving region (Hockley et al, 2013), protecting the species from predators, and finally increasing biomass and diversity. Quantification of these elements in terms of physical measures has been carried out (Kim et al, 2016b), for example efficiency, tranquility, and stability indices of an AR wake region.…”
Section: Introductionmentioning
confidence: 99%